Nurses' attitudes to a medical emergency team service in a teaching hospital. Issue 6 (1st December 2006) - Jones, D; Baldwin, I; McIntyre, T; Story, D; Mercer, I; Miglic, A; Goldsmith, D; Bellomo, R
Abstract : Background: Cultural barriers including allegiance to traditional models of ward care and fear of criticism may restrict use of a medical emergency team (MET) service, particularly by nursing staff. A 1-year preparation and education programme was undertaken before implementing the MET at the Austin Hospital, Melbourne, Australia. During the 4 years after introduction of the MET, the programme has continued to inform staff of the benefits of the MET and to overcome barriers restricting its use. Objective: To assess whether nurses value the MET service and to determine whether barriers to calling the MET exist in a 400-bed teaching hospital. Methods: Immediately before hand-over of ward nursing, we conducted a modified personal interview, using a 17-item Likert agreement scale questionnaire. Results: We created a sample of 351 ward nurses and obtained a 100% response rate. This represents 50.9% of the 689 ward nurses employed at the hospital. Most nurses felt that the MET prevented cardiac arrests (91%) and helped manage unwell patients (97%). Few nurses suggested that they restricted MET calls because they feared criticism of their patient care (2%) or criticism that the patient was not sufficiently unwell to need a MET call (10%). 19% of the respondents indicated that MET calls are required because medical management by the doctors has been inadequate; many ascribed this to junior doctors and a lack of knowledge and experience. Despite hospital MET protocol, 72% of nurses suggested that they would call the covering doctor before the MET for a sick ward patient. However, 81% indicated that they would activate the MET if they were unable to contact the covering doctor. In line with hospital MET protocol, 56% suggested that they would make a MET call for a patient they were worried about even if the patient's vital signs were normal. Further, 62% indicated that they would call the MET for a patient who fulfilled MET physiological criteria but did not look unwell. Conclusions: Nurses in the Austin Hospital value the MET service and appreciate its potential benefits. The major barrier to calling the MET appears to be allegiance to the traditional approach of initially calling parent medical unit doctors, rather than fear of criticism for calling the MET service. A further barrier seems to be underestimation of the clinical significance of the physiological perturbations associated with the presence of MET call criteria.